Factors Affecting Occupational Safety and Health Behavior in Welding Workshop Workers - Sugiarto; Melda Yenni; T Samsul Hilal (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: Accidents are generally caused by workers not applying a safety act in welding work, improper use of protective equipment, improper environmental regulation Objectives: This study aims to determine the factors related to occupational safety and health behavior in welding workshop workers. Research Metodes: This research is a quantitative study with an observational approach using a cross sectional design. The research sample was 52 welding workshop workers in Suka Karya Village, Jambi City. The sampling technique was purposive sampling. The instrument used was a questionnaire. Data collection techniques by interview. Findings: Bivariate results show that there is a relationship between knowledge (p = 0.000), attitude (p = 0.004) and occupational safety and health facilities (p = 0.003) with the behavior of implementing occupational safety and health among welding workshop workers in Suka Karya Village. Conclusion: Occupational safety and health behavior in welding workshop workers is related to knowledge, attitudes, and facilities Keywords: occupational safety and health behavior